Ellen White, the Scripture, and the issue of Authority: A Historical Overview - R. Knight, George (2016)
Seventh-day Adventists claims that the Word of God in the Bible contains the “knowledge necessary for salvation,” is the source of doctrine, and “is the standard by which all teaching and experience must be tested,” but also maintain that Ellen G. White had a valid and “authoritative” prophetic gift. Here arises the important question for us: do Ellen G. White‘s writings have the same authority than the Bible? In order to answer this question, this study will focus on showing the relationship between Ellen G. White’s authority and the authority of the Bible in Adventism from a historical perspective